2010
DOI: 10.1007/s10344-010-0430-9
|View full text |Cite
|
Sign up to set email alerts
|

Hares in Corsica: high prevalence of Lepus corsicanus and hybridization with introduced L. europaeus and L. granatensis

Abstract: The Italian hare, Lepus corsicanus, was first described in Corsica more than 100 years ago, but the knowledge on the status of the species in this island remains scarce. Moreover, frequent introductions of thousands of individuals from other hare species, namely Lepus europaeus and Lepus granatensis, into Corsica are known to have occurred and an updated assessment of the prevalence of L. corsicanus in Corsica is therefore of utmost importance. Here, to estimate the relative prevalence of the hare species pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…The occurrence of brown hares in southern Italy is the consequence of recent translocations of non-indigenous hares, and of captive-reproduced stocks that were released for hunting purposes. Therefore those two hares could have originated from natural introgression of Italian hare mtDNA in brown hares or from the undocumented releases of captive-reproduced hybrids (Pietri et al 2011 reported two cases of putative Italian hare x brown hare hybrids in Corsica). Natural hybridization in Italian hares outside their native habitats could be not excluded, as it could be not excluded that these two individuals originated from the release of captivereproduced hybrids.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The occurrence of brown hares in southern Italy is the consequence of recent translocations of non-indigenous hares, and of captive-reproduced stocks that were released for hunting purposes. Therefore those two hares could have originated from natural introgression of Italian hare mtDNA in brown hares or from the undocumented releases of captive-reproduced hybrids (Pietri et al 2011 reported two cases of putative Italian hare x brown hare hybrids in Corsica). Natural hybridization in Italian hares outside their native habitats could be not excluded, as it could be not excluded that these two individuals originated from the release of captivereproduced hybrids.…”
Section: Discussionmentioning
confidence: 94%
“…As far as we know, historical introgression has been excluded, but ongoing anthropogenic hybridization may still threaten the integrity of the Italian hare gene pool (Pierpaoli et al 1999;Thulin et al 2006). However, studied Italian hare populations were typed using almost only uniparental mtDNA sequences (but see Pietri et al 2011), which may not document the effective degree of reproductive isolation or recent gene flow among contact populations.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, European hares, Iberian hares and Apennine hares are also known to have hybridized in ancient times (Pietri et al. ). The phenomenon is pervasive, being present also in Asia (Liu et al.…”
Section: Review and Discussionmentioning
confidence: 99%
“…There is evidence suggesting that hybridisation was common during Pleistocene glaciations between Lepus timidus, Lepus granatensis, Lepus europaeus, and Lepus castroviejo (Melo-Ferreira et al 2007, Alves et al 2008, and it continues in the present. For instance, genetic evidence shows that Lepus corsicanus is suffering from the effects of hybridisation due to the introduction of Lepus europaeus and Lepus granatensis, which are deteriorating the gene pool of this Vulnerable species (Pietri et al 2011). In Sweden, introduced Lepus europaeus hybridise with Lepus timidus, and, even when gene introgression appears to be low, behavioural differences between the males (where Lepus europaeus males guard females, preventing mating with their conspecifics) may cause the loss of species-specific litters (Thulin 2003, Jansson et al 2007.…”
Section: Effects On Other Herbivoresmentioning
confidence: 99%